Urgent transcatheter aortic valve replacement may be performed with acceptable long‐term outcomes. Issue 1 (22nd November 2020) - Bianco, Valentino; Habertheuer, Andreas; Kilic, Arman; Aranda‐Michel, Edgar; Serna‐Gallegos, Derek; Schindler, John; Kliner, Dustin; Toma, Catalin; Zalewski, Adrian; Sultan, Ibrahim
Abstract: Background: The wide availability of transcatheter aortic valve replacement (TAVR) and broadening of its indications to most patients with aortic stenosis may increase its utilization in the urgent setting. However, a comparison of long‐term outcomes of patients undergoing urgent TAVR when compared to elective TAVR have not been well studied. Methods: All patients that underwent TAVR from 2011 to 2018 were included. Primary outcomes included operative (30‐day), 1‐, and 5‐year survival and readmissions. Results: The total patient population undergoing TAVR was divided into urgent ( n = 247) and elective ( n = 946) cohorts. Thirty days mortality (6.5% vs. 2.3%; p = .001), acute kidney injury (2.8% vs. 0.6%; p = .003), and length of stay (12 vs. 3 days; p < .001) were higher for the urgent cohort. There was no significant difference between cohorts for 30‐day all‐cause (14.6% vs. 10.8%; p = .097) readmissions. Freedom from readmission for heart failure at 1‐year (73.6% vs. 83.4%; p < .001) was lower for the urgent cohort. One‐ (79.0% vs. 87.1%; p < .001) and five‐year (39.6% vs. 43.5%; p = .005) survival was lower for the urgent cohort. This difference was eliminated after risk adjustment (hazard ratio [HR]: 1.3; p = .158 and HR: 1.1; p = .639, respectively). Conclusion: Unadjusted survival was significantly worse for the urgent cohort up to 1 year. This trend continued for 5‐year survival, however, after risk adjustment there was no significant difference in survival between cohorts. Although urgent TAVR is associated with increased periprocedural risk due to more comorbid disease, outcomes and long‐term survival are encouraging and support the consideration of urgent TAVR as a viable alternative for this patient population.